Convulsant Doses of a Dopamine D1 Receptor Agonist Result in Erk-Dependent Increases in Zif268 and Arc/Arg3.1 Expression in Mouse Dentate Gyrus - Gangarossa, Giuseppe (Public Library of Science, 2011)
Activation of dopamine D1 receptors (D1Rs) has been shown to induce epileptiform activity. We studied the molecular changes occurring in the hippocampus in response to the administration of the D1-type receptor agonist, SKF 81297. SKF 81297 at 2.5 and 5.0 mg/kg induced behavioural seizures. Electrophysiological recordings in the dentate gyrus revealed the presence of epileptiform discharges peaking at 30–45 min post-injection and declining by 60 min. Seizures were prevented by the D1-type receptor antagonist, SCH 23390, or the cannabinoid CB1 receptor agonist, CP 55,940. The effect of SKF 81297 was accompanied by increased phosphorylation of the extracellular signal-regulated protein kinases 1 and 2 (ERK), in the granule cells of the dentate gyrus. This effect was also observed in response to administration of other D1-type receptor agonists, such as SKF83822 and SKF83959. In addition, SKF 81297 increased the phosphorylation of the ribosomal protein S6 and histone H3, two downstream targets of ERK. These effects were prevented by genetic inactivation of D1Rs, or by pharmacological inhibition of ERK. SKF 81297 was also able to enhance the levels of Zif268 and Arc/Arg3.1, two immediate early genes involved in transcriptional regulation and synaptic plasticity. These changes may be involved in forms of activity-dependent plasticity linked to the manifestation of seizures and to the ability of dopamine to affect learning and memory.